Exercise inhibits JNK pathway activation and lipotoxicity via macrophage migration inhibitory factor in nonalcoholic fatty liver disease - Cui, Ni; Li, Hui; Dun, Yaoshan; Ripley-Gonzalez, Jeffrey W.; You, Baiyang; Li, Dezhao; Liu, Yuan; Qiu, Ling; Li, Cui; Liu, Suixin (Frontiers in Endocrinology, 2022)
Macrophage migration inhibitory factor (MIF) expressed in hepatocytes could limit steatosis during obesity. Lipotoxicity in nonalcoholic fatty liver disease is mediated in part by the activation of the stress kinase JNK, but whether MIF modulates JNK in lipotoxicity is unknown. In this study, we investigate the role of MIF in regulating JNK activation and high-fat fostered liver lipotoxicity during simultaneous exercise treatment. Fifteen mice were equally divided into three groups, normal diet, high-fat diet, and high-fat and exercise group. High-fat feeding for extended periods elicited evident hyperlipemia, liver steatosis, and cell apoptosis in mice, with inhibited MIF and activated downstream MAPK kinase 4 phosphorylation and JNK. These effects were then reversed following prescribed swimming exercise, indicating that the advent of exercise could prevent liver lipotoxicity induced by lipid-overload and might correlate to the action of modulating MIF and its downstream JNK pathway. Similar detrimental effects of lipotoxicity were observed in in vitro HepG2 cells Palmitic acid treatment. Suppressed JNK reduced the hepatocyte lipotoxicity by regulating the BCL family, and the excess JNK activation could also be attenuated through MIF supplementation or exacerbated by MIF siRNA administration. The results found suggest that exercise reduces lipotoxicity and inhibits JNK activation by modulating endogenous hepatic MIF in NAFLD. These findings have clinical implications for the prevention and intervention of patients with immoderate diet evoked NAFLD.